Antioxidant potency of mangosteen peel extract topical application in reversing reduced orthodontic brackets tensile strength after bleaching - Ananto Ali Alhasyimi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Nowadays, cosmetic dentistry has become an ever-increasing requirement with interest in it growing over time. Bleaching is one of the popular cosmetic treatments that has been proven to diminish the tensile bond strength (TBS) of orthodontic brackets attached to bleached teeth. Mangosteen peel (MP) extract contains antioxidants that may potentially reverse the reduction in TBS. Purpose: The purpose of this study was to evaluate the effect of MP extract on the post- bleaching TBS of brackets. Methods: The reported research constitutes an experimental in vitro study conducted on a total of 120 maxillary first premolar teeth randomly divided into six groups (n = 20) as follows: negative-control (NC: no bleaching), positive-control (PC: bleaching + no treatment), and the treatment groups (bleaching + 10% sodium ascorbate (SA), 10% (MP10), 20% (MP20) and 40% (MP40) MP extract gel). Post-treatment, the brackets were bonded using Transbond XT and TBS testing was performed using a Universal Testing Machine. The ARI was examined by means of a stereoscopic microscope, while enamel morphological changes were observed through a Scanning Electron Microscope. The TBS-generated data was analyzed by means of Anova and Tukey tests. For the Adhesive Remnant Index, a Kruskal-Wallis analysis test was performed. Results: There was a significant TBS difference (P = 0.001) between the various groups. The PC group showed the significantly highest TBS compared to the others (8.33 ± 3.92 MPa), whereas NC demonstrated the lowest (4.15 ± 2.27 Mpa). The TBS value of the MP40 group was considerably higher than other groups treated with antioxidants (7.87 ± 3.26 MPa). The failure of orthodontic brackets using MP extract mostly occurred at the adhesive-bracket interfaces. Conclusion: Topical application of 40% mangosteen peel (MP) extract as an antioxidant after bleaching was effective in reversing the reduced post-bleaching tensile bond strength (TBS) of orthodontic brackets.